Effect of annealing and nitridation on (0001) sapphire surface polaritons. Issue 3 (24th January 2013) - Zhuravlev, Konstantin; Malin, Timur; Mansurov, Vladimir; Novikova, Nadezhda; Yakovlev, Vladimir; Toropov, Alexey; Ivanov, Sergey
Abstract The effect of annealing temperature on nitridation process of (0001) Al2O3 surface under ammonia flux was investigated by high‐energy electron diffraction and surface polaritons spectroscopy. High temperature annealing (≥1150 °C) of the surface results in the surface reconstruction √31×√31R±9° that inhibits the nitridation process. The external reflectivity infrared spectroscopy at near normal incidence angle is not sensitive to the annealing and nitridation. On the other hand, the high‐frequency minimum in the attenuated total reflection spectra splits near 700 cm–1 due to the surface reconstruction and/or the presence of aluminum nitride on the substrate surface, the splitting is sensitive to the surface treatment. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)